Strategi Pengembangan Wisata Mangrove Desa Sedari Berbasis Analisis 4A (Attraction, Accessibility, Amenities, Ancillary Services) - Millenia, Jane; Sulivinio, Shirley; Rahmanita, Myrza; Osman, Ismeth Emier (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2021)
The development of mangrove forest tourism in Sedari Village, Karawang Regency has obstacles related to tourism components as limited attractions, narrow roads, damaged facilities and so on. This condition requires an effective strategy so that tourism continues to grow. Therefore, this research on the Strategy for Development of Sedari Village Mangrove Tourism Based on the 4A Analysis (Attraction, Accessibility, Amenities, Ancillary Services) was carried out. This study aims to explore the development strategy of mangrove forest tourism in Sedari village based on condition 4 A. This study used a descriptive qualitative approach, and data were obtained through interviews and literature study using the SWOT analysis method (Strengths, Weaknesses, Opportunities and Threats). The result of this research is the strength opportunity (SO) value is 4.11, the weakness opportunity (WO) strategy is 3.75, the strength threats (ST) strategy is 2.68 and the weaknesses threats (WT) strategy is 2.52. Sedari Village Mangrove Tourism prioritizes using the SO strategy, namely collaborating with academics and mangrove experts for mangrove development and management, designing and conducting training programs for processing mangroves into products, creating economic income opportunities by increasing mangrove-based Sedari Village production and maintaining mangrove tourism ecotourism by still pay attention to the carrying capacity of the area. Keywords: Sedari Village, Attractiveness, Accessibility, Amenities, Ancillary Services, SWOT